Development Strategy of Mangrove Ecotourism Centre at Pantai Indah Kapuk as an Attraction at DKI Jakarta - Okky Febriyanto (Geo Media: Majalah Ilmiah dan Informasi Kegeografian, 2020)
Mangrove Ecotourism Centre Pantai Indah Kapuk is a tourism destination in Jakarta that managed by Ministry of Forestry. Mangrove ecosystem at Mangrove Ecotourism Centre Pantai Indah Kapuk has natural resources for ecotourism. From that potential, can defined the accurate strategy for Mangrove ecosystem at Mangrove Ecotourism Centre Pantai Indah Kapuk developing. The result showed that the determined alternative strategy aim to reach the short term and long term objective at Mangrove Ecotourism Centre Pantai Indah Kapuk, that is develop all potential which covering destination, promotion and human resources owned as an alternative tourism by focusing on sustainable tourism in the capital city of Indonesia, DKI Jakarta. Creates opportunities for coaching people around the destination to do development and management of mangrove to increase public income. Create synergy among developer, government,community, and the third parties in the development of destination, promotion and human resources to reach a joint purpose.